Efektivitas Penerapan Jobsheet pada Mata Pelajaran Estimasi Biaya Konstruksi Siswa Desain Pemodelan Dan Informasi Bangunan SMK Negeri 1 Kediri - Anissa Yuniarsih; Agus Wiyono (Jurnal Kajian Pendidikan Teknik Bangunan, 2024)
This study has the following objectives: (1) To determine the feasibility of jobsheet media in the subject of construction cost estimation, (2) To determine the learning outcomes of students of SMK Negeri 1 Kediri, (3) To determine the students' responses to learning media. The methodology of this study is research and development (Research and development) utilizing the four-D Models development model consisting of 4 stages such as: 1) Define, 2) Design, 3) Develop, 4). Dissemination. From the results of the analysis and discussion obtained regarding: 1) jobsheet products that help learning are the result of this development research, 2) The level of feasibility was obtained from the assessment results of material and media experts and student responses with an average of 79.7% from the results of the validation of material experts which included the very feasible classification. The results of the validation of media experts had an average of 80.1% which means very feasible. According to student responses, an average value of 81% was obtained which means students gave a positive response. The results of the t-test also explain the sig value <0.05, meaning that there is an influence between classes that use jobsheets and those that do not. It is recommended that further researchers distribute jobsheets to other schools, not only to the schools studied.